Sinergi Hukum Islam dan Hukum Positif dalam Penyelesaian Sengketa Ekonomi Syariah di Indonesia - Ananda, Rizqa; Wahdah, Wahdah; Wahidah, Wahidah; Hasan, Ahmadi; Mariani, Mariani (Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory, 2026)
The preservation of the sharia economy is increasingly important due to the rapid growth of sharia-based financial institutions and economic activities. This study aims to analyze the synergy between Islamic law and positive law in resolving sharia economic issues in Indonesia. The method used is a normative qualitative research with a juridical approach based on literature study. Data were obtained from primary sources (regulations and Islamic legal concepts), secondary sources (books, scientific journals), and tertiary sources (general legal literature). The analysis was conducted inductively and descriptively to identify conceptual relationships between rules. The results of the study indicate that Islamic law facilitates dispute resolution through the principles of al-sulh (peace), tahkim (arbitration), and wilayat al-qadha (court). Meanwhile, Indonesian positive law provides alternative ADR (negotiation, mediation, arbitration) and support from judicial institutions (Religious Courts) that regulate legislation. The results of this study can be concluded that the synergy between these two legal systems is integral, encompassing the values ​​of justice ('adl), benefit, and legal certainty in resolving sharia economic issues. This integration needs to be strengthened through education and clear regulations to overcome the obstacles to judges' understanding and the overlaps that occur.